PT Garam's Salt Pricing Strategy In Maintaining Salt Price Stability at The Farmer Level - Indra Kurniawan (Publikasi Indonesia, 2024)
The purpose of the study is PT Garam's Salt Pricing Strategy In Maintaining Salt Price Stability at The Farmer Level. This research design uses a quantitative research approach This type of research uses descriptive research methods. By paying attention to the SWOT matrix, the strategy that can be done by the company is to lay a solid foundation to prepare itself for excellent performance on farm by modernizing and mechanizing fencing, infrastructure development, preparing human resource and corporate capacity building the off farm sector through downstream salt derivative chemical industries (Soda Ash Factory, Cosmic Soda and Pharmaceutical Salt) as well as strengthening marketing and sales strategies to strengthen PT Garam's product brand and Increase market share for processed salt (both table salt and lifestyle salt). Other potentials are affirming the legality of ownership of PT Garam (Persero) Surabaya office, port cooperation with private and state-owned enterprises, changing the ownership status of Garam Islamic Hospital, developing and optimizing the area around the head office of PT Garam (Persero) in Kalianget as heritage and tourist visits.